Research on the preparation and self-healing performance of microwave-induced functional steel slag asphalt mixture - Chao Chen; Qinhao Deng; Chuangmin Li; Shuaibing Yi; Lubiao Liu (Case Studies in Construction Materials, 2024)
This study explores the potential applications of steel slag and tire pyrolysis oil (TPO) in creating self-healing road construction materials, aiming to address environmental concerns related to industrial waste and to extend the service life of roadways. A novel functional steel slag asphalt mixture was developed, utilizing steel slag as the aggregate and TPO as a healing agent. This agent permeates the pores of the steel slag, with microwave induction facilitating its controlled release. The research embarked on identifying the optimal process for preparing the functional steel slag aggregate through orthogonal experiments. It puts forward the optimum parameters of microwave induction based on the results of the low-temperature bending beam test and evaluates the effectiveness of the microwave-induced asphalt mixture’s self-healing. The study revealed that the recommended process for preparing functional steel slag aggregates is vacuuming the steel slag submerged in TPO for 30 minutes, followed by a soaking period of 10 minutes under standard atmospheric pressure, and concluding with a 48-hour standing period after removal from the TPO. Under this process, the absorption rate of TPO by steel slag reaches its maximum. Employing the Marshall test design method, the optimal asphalt-aggregate ratio was determined to be 5.15%. Significantly, the microwave heating rate of the functional steel slag asphalt mixture was found to be 3.25 times that of a conventional limestone asphalt mixture. The recommended microwave induction parameters were established at 700 W of power for a duration of 80 seconds. Initially, the crack healing rate reached 64.6%, which decreased to 47.6% after five microwave cycles. Remarkably, the healing rate of the functional steel slag asphalt mixture outperformed that of the ordinary steel slag asphalt mixture without TPO by 69.5% after the same number of cycles. These findings offer valuable contributions to the development of self-healing road construction materials, presenting a promising path for enhancing the durability of road infrastructures while addressing environmental challenges posed by industrial waste.